REFERENCES OF DISCOURSE AND ITS TYPES IN AKSHATA MURTHY: UK’S FIRST LADY SPEECH - Siti Tasya Jelita Manurung (Universitas Negeri Medan, 2023)
This study examined the references used in Akshata Murthy's speech